A Domino Palladium Catalysis: Synthesis of 7-Methyl-5H-dibenzo[a,c][7] annulen-5-ones - Krishna, Jonnada; Gopi Krishna Reddy, Alavala; Satyanarayana, Gedu (Synlett, 2013)
A domino Pd-catalyzed reaction of 1-(2-bromophenyl)ethanones for the synthesis of novel 7-methyl-5H-dibenzo[a,c][7]annulen-5-ones, a carbon core structure present in colchicinoid natural products, is presented. The reaction is proposed to proceed via intermolecular homobiaryl coupling and intramolecular aldol condensation.
Keywords: Pd catalysis; homobiaryl coupling; domino reaction; aldol condensation; 2-bromoacetophenones